Optimization of Community Roles in Building an Arabic-speaking Environment at Darussalam Blokagung Banyuwangi Pesantren - Anyes Lathifatul Insaniyah; Yayah Robiatul Adawiyah (Simfoni Ilmu Cindekia, 2025)
This community service activity aims to optimize the community's efforts in creating and maintaining an active Arabic-speaking environment at Pesantren Darussalam Blokagung Banyuwangi. Although Arabic is the foundation of Islamic scholarship, there are often conflicts between the language and its usage in the pesantren environment. The methods to achieve the goals of this PKM project include primary and secondary instructional training, participatory workshops, intensive training for students and teachers, as well as mentoring in developing community initiative projects, such as language clubs, Arabic speaking weeks, and internal Arabic language communication media. This approach involves all elements of the community and pesantren, including the society and management, teachers, and all students. Feedback from participants indicates significant improvements in students' motivation and confidence to communicate in Arabic, as well as the emergence of various independent initiatives from the pesantren community to strengthen the Arabic-speaking environment. The optimization of community efforts has proven effective in building a sustainable language ecosystem, nurturing a more dynamic Arabic-speaking culture, and reinforcing the scholarly identity of the pesantren.